A comparison study on structure-function relationship of polysaccharides obtained from sea buckthorn berries using different methods: antioxidant and bile acid-binding capacity - Qiaoyun Li; Zuman Dou; Qingfei Duan; Chun Chen; Ruihai Liu; Yueming Jiang; Bao Yang; Xiong Fu (Food Science and Human Wellness)
In this study, the structural characters, antioxidant activities and bile acid-binding ability of sea buckthorn polysaccharides (HRPs) obtained by the commonly used hot water (HRP-W), pressurized hot water (HRP-H), ultrasonic (HRP-U), acid (HRP-C) and alkali (HRP-A) assisted extraction methods were investigated. The results demonstrated that extraction methods had significant effects on extraction yield, monosaccharide composition, molecular weight, particle size, triple-helical structure, and surface morphology of HRPs except for the major linkage bands. Thermogravimetric analysis showed that HRP-U with filamentous reticular microstructure exhibited better thermal stability. The HRP-A with the lowest molecular weight and highest arabinose content possessed the best antioxidant activities. Moreover, the rheological analysis indicated that HRPs with higher galacturonic acid content and molecular weight showed higher viscosity and stronger crosslinking network (HRP-C, HRP-W and HRP-U), which exhibited stronger bile acid binding capacity. The present findings provide scientific evidence in the preparation technology of sea buckthorn polysaccharides with good antioxidant and bile acid binding capacity which are related to the structure affected by the extraction methods.